KAJIAN KUALITAS PERAIRAN LAUT KOTA SEMARANG DAN KELAYAKANNYA UNTUK BUDIDAYA LAUT - Agung Riyadi (Jurnal Teknologi Lingkungan, 2005)
Marine culture develoment at Semarang Central java coast is notincreased. Based on water quality, a good water quality conditions at line 3,beside far for human activities, the dissolved oxygen and turbidity level stillsuitable for marine culture activities. The dissolved oxygen value from 4.8 – 5mg/l. Comparing with the second station (line l and 2) dissolved oxygen (DO) israther low and turbidity level is very hight, turbidity value until 4 FTU. The method using digital device Chlorotech type AAQ 1183, Alecs Electronics for describing the characteristicsof tropical coastal hydrography and water quality.